Fruit set and fruit size studies on ‘Forelle’ and ‘Abate Fetel’ pear (Pyrus communis L.) - Dreyer, Carlien (Stellenbosch : Stellenbosch University, 2013)
Thesis (MScAgric)--Stellenbosch University, 2013.